The Students’ Perception Towards Teacher Code Switching in Teaching English as Foreign Language at STISIPOL Candradimuka Palembang - Sherly Desliyanah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The purpose of this study is to ascertain how students at STISIPOL Candradimuka Palembang feel about teachers using code switching when teaching English. The study sample consisted of 37 students from the Social Welfare Science course. The Qualitative survey research design was applied in this study. The questionnaire was spread to the students as the research instrument to investigate students’ perception. The result of the questionnaire was analyzed by using the Likert scale to know the degree of agreement and disagreement. The study's findings demonstrated that students had a positive perception of teachers who code-switch between Indonesian and English because it makes learning the language more fun and motivates them to try having conversations in it.